Faktor Penyebab Terjadinya Perceraian di Pengadilan Agama Serang - Sa'adiyyah, Ade Millatus; Aulawi, Anton; Apriliani, Senah (Ajudikasi : Jurnal Ilmu Hukum, 2023)
Divorce is the final point of a marriage that is unable to achieve the noble goal of family happiness as expected by every married couple. This study aims to find out about the factors that cause divorce in the Serang Religious Court. To achieve these objectives, the researchers used descriptive research with a qualitative approach. Informants in this study were judges, junior clerks and Posbakum. Data collection was carried out using the method of observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and conclusion. Based on the research results, it was found that the highest causes of divorce in the Serang Religious Courts were (1) Continuous Quarrels and Disputes (47%), (2) Economics (36%), (3) Domestic Violence (12%), (4) Leaving one of the parties (5%), and the consequences of divorce are very broad and complex, because it is not only the divorced husband and wife who feel the consequences of the divorce but also the impact on children and wealth.